2002
DOI: 10.3354/meps243209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water temperature changes on the endogenous and exogenous rhythms of oxygen consumption in glass eels Anguilla japonica

Abstract: The oxygen consumption rate (OCR) of glass eels Anguilla japonica was measured to determine the effects of water temperature changes on their endogenous and exogenous rhythms. Glass eels were exposed to different water-temperature patterns during simulated 12, 14 and 24 h cycles. The OCR of wild glass eels, freshly collected from estuaries, exhibited a clear endogenous circatidal rhythm while kept in constant darkness at 15 ± 0.1°C. However, if the temperature was varied, the glass eels OCR coincided with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Slight temperature changes may induce phase shifting of endogenous rhythms through alterations of the clock molecular machinery (Rensing and Ruoff 2002). Accordingly, in A. japonica glass eels kept under free-running conditions, a slight temperature change may shift the rhythm of the internal circatidal clock (Kim et al 2002). Such temperature-mediated phase shifting in the internal tidal clock may be one of the processes leading to an inefficient use of tidal streams by glass eels (see Fig.…”
Section: Tidal Streams: the Importance Of Ststmentioning
confidence: 99%
“…Slight temperature changes may induce phase shifting of endogenous rhythms through alterations of the clock molecular machinery (Rensing and Ruoff 2002). Accordingly, in A. japonica glass eels kept under free-running conditions, a slight temperature change may shift the rhythm of the internal circatidal clock (Kim et al 2002). Such temperature-mediated phase shifting in the internal tidal clock may be one of the processes leading to an inefficient use of tidal streams by glass eels (see Fig.…”
Section: Tidal Streams: the Importance Of Ststmentioning
confidence: 99%
“…It is reported that when the glass eels were exposed to a cyclic increase or decrease in water temperature (1℃/14 h), the OCR peaks displayed a clear rhythmicity at 14 h intervals (Kim et al, 2002a). Therefore, our observation of eels' thermal limits which may affect physiological state and the survival of the eels, can offer a meaningful information for appropriation of optimal temperature in the eel culture.…”
Section: Discussionmentioning
confidence: 67%
“…The relationship between the endogenous rhythm and the environmental factors should be defined to understand physiological and behavioral aspects of this species. However, few data are available on the correlation between water temperature changes and metabolic activity rhythms in adult eels (Kim et al, 2002a). …”
Section: Introductionmentioning
confidence: 99%
“…2) following the procedures described by Kim et al(1996Kim et al( , 1998Kim et al( , 2002. To obtain the concentration in mg/L, the following formula was used to convert the gas volume under standard conditions, V std , into the gas volume under measured conditions, V R :…”
Section: Experimental Designmentioning
confidence: 99%